STRATEGI PENGEMBANGAN USAHA TERNAK SAPI POTONG DI KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR (Beef Cattle Business Development Strategy in Kupang District, East Nusa Tenggara Province) - Soluf, Morin Mediviani; Sabat, Diana Meliani (Universitas Nusa Cendana, 2025)
The purpose of this study is to identify various internal and external factors and determine the appropriate strategy for the development of beef cattle in Kupang District. This study employs both quantitative and qualitative approaches, with respondents selected through purposive sampling. The data collected were analyzed using SWOT analysis to identify Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE), and the Quantitative Strategic Planning Matrix (QSPM) to determine the primary strategic alternatives. The analysis results indicate that beef cattle farming in Kupang Regency has three strengths, three weaknesses, three opportunities, and four threats. Based on the SWOT analysis, the IFE value is 3,39 and the EFE value is 2,43 reflecting the potential for beef cattle development. The results of the QSMP analysis indicate that the recommended priority strategy is to diversify marketing channels and institutions by leveraging the strengths of farmers to address threats such as long marketing chains, inadequate infrastructure conditions, and price fluctuations through institutional strengthening and marketing chain efficiency. The conclusion of this study is that beef cattle farming in Kupang District is in a strong internal position to face external threats with the priority strategy of diversifying distribution and institutional structures.